Android application for emergency care - Ho, Adonas Jue Ting (2017)
Glancing over the modern world nowadays, almost everyone locating in different region of the world at least own a smartphone, regardless of the Operating System it is using. With smartphones coming into the picture, communication became a much bigger role compared to the history of how communication devices happened to be in the early days. Additionally, with the evolution of electronics components getting smaller and smaller, they are incorporated into almost all the electronic devices which the human race are using nowadays, which in turn, changes the lifestyles and accessibility of people in the society, leading to higher demand of changing the older technologies to a higher level to make life easier and moving into a “smarter” world concurrently.